Prevalence of porcine respiratory pathogens in slaughterhouses in Shanxi Province, China. Issue 4 (22nd May 2021) - Yue, Weidong; Liu, Yihui; Meng, Yukai; Ma, Haili; He, Junping
Abstract: Background: Porcine respiratory diseases remain the biggest challenge in pig‐based food production and are a public health concern. Despite control measures, persistent outbreaks have been reported worldwide. Objective: To establish an early detection mechanism for pig farm disease outbreaks based on slaughterhouse risk and environmental assessment. Methods: We investigated the prevalence and risk factors of porcine respiratory disease‐causing pathogens including Mycoplasma hyopneumoniae (MHP), porcine circovirus type 2 (PCV2), porcine reproductive and respiratory syndrome virus (PRRSV) and Haemophilus parasuis (HPS). Polymerase chain reaction (PCR) was used to analyse the lungs of 491 pigs from 19 slaughterhouses across 11 cities in Shanxi Province, China. Results: PCR detected MHP, PCV2, PPRSV and HPS in 76.99%, 67.00%, 11.82% and 19.55% of the samples, respectively; 10.12% were negative for all four pathogens. Co‐positivity rates for two and three pathogens were identified. The results confirmed significant correlations between PCV2 and MHP ( p  = .001, p  < .05), HPS and PCV2 ( p  = .01, p  < .05) and MHP and PRRSV ( p  = .01, p  < .05). No significant correlation was observed between HPS and MHP ( p  = .067, p  > .05). Positive MHP and PCV2 rates were low in areas with high vegetation coverage. The overall pathogen positivity rate was higher in both lower and higher temperature environments. Conclusions: Interactions among pathogens may increase disease severity. Furthermore, environmental assessment and pathogen surveillance within pig slaughterhouses can be an effective approach for early detection and mitigation of new disease threats before broad dissemination occurs among a herd. Abstract : It is a comprehensive epidemiological survey of Mycoplasma hyopneumoniae (MHP), Porcine circovirus type 2 (PCV‐2) and Haemophilus parasuis (HPS) infection in pig in Shanxi of China. 2. The meteorological factors and geographic area might be important variables affecting the transmission of porcine respiratory pathogens. The study suggested that interactions between pathogens might increase the severity of porcine respiratory disease outcomes.